18 Bsci/bscct research sub-committee survey of research activity and cardiovascular imaging research priorities. (15th May 2019) - Yong, Guoliang; Weir-McCall, Jonathan; Wilson, Michael; Roditi, Giles; Williams, Michelle C; Schmitt, Matthias
Abstract : Aim: The BSCI/BSCCT research sub-committee survey aims to assess research activity and barriers to research amongst the society members. In addition, a modified Delphi approach will be used to develop consensus opinion for prioritising research questions in cardiovascular imaging amongst BSCI/BSCCT members. Methods: All members of the BSCI/BSCCT have been invited to participate in the online survey. The survey covers whether people are currently involved in research or would like to be involved in research or audit, what are the perceived barriers to involvement in research, and the ways that the BSCI/BSCCT may be able to support the research community. A modified Delphi approach with three rounds of surveys will be conducted to establish research priorities in cardiovascular imaging amongst BSCI/BSCCT members. Research questions will be collected during the first survey, followed by two rounds of prioritisation. A steering group will analyse results of each round and identify questions ranked as being the highest priority for each subsequent round of the Delphi process. Results: We will present the initial results of this survey including current research activity, barriers to research and initial research question suggestions. Conclusion: It is anticipated that this modified Delphi process will establish research priorities in cardiovascular imaging which will be used to plan other BSCI/BSCCT activities.